2018
DOI: 10.2135/cropsci2018.02.0128
|View full text |Cite
|
Sign up to set email alerts
|

Herbage Responses and Biological N2 Fixation of Bahiagrass and Rhizoma Peanut Monocultures Compared with their Binary Mixtures

Abstract: Bahiagrass (Paspalum notatum Flüggé) and rhizoma peanut (RP, Arachis glabrata Benth.) are widely used in Florida, and growing them in association may decrease the need for N fertilization. This study evaluated herbage responses of mixed RP-bahiagrass swards in comparison with their monocultures. The eight treatments were two bahiagrass entries ('Argentine' and DF9, receiving 90 kg N ha −1 harvest −1 ) and two RP entries (Ecoturf and Q6B) in monoculture and the combinations of each bahiagrass with each RP (Arge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 41 publications
(126 reference statements)
0
30
1
Order By: Relevance
“…Herbage accumulation of Beta was greater than that reported by Santos et al. (2018) in a 2‐yr experiment in which Beta (5.4 Mg ha −1 yr −1 ) and the germplasm Ecoturf RP were harvested by clipping four times per year. In that study, annual HA of Ecoturf was 5.0 Mg ha −1 compared with 3.9 Mg ha −1 (1× treatment) and 10.5 Mg ha −1 (2× treatment) in the current experiment.…”
Section: Resultscontrasting
confidence: 55%
“…Herbage accumulation of Beta was greater than that reported by Santos et al. (2018) in a 2‐yr experiment in which Beta (5.4 Mg ha −1 yr −1 ) and the germplasm Ecoturf RP were harvested by clipping four times per year. In that study, annual HA of Ecoturf was 5.0 Mg ha −1 compared with 3.9 Mg ha −1 (1× treatment) and 10.5 Mg ha −1 (2× treatment) in the current experiment.…”
Section: Resultscontrasting
confidence: 55%
“…In general, bahiagrass ( Paspalum notatum Flügge), and bermudagrasses ( Cynodon spp. ), two of the most common pasture species in the southeastern United States, tend to have CP concentrations ranging between 80 and 120 g/kg, and digestibility ranging between 400 and 520 g/kg (Agyin‐Birikorang, Newman, & Kasozi, 2012; Jaramillo et al, 2018; Santos et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…According to Stevenson et al (2010), others processes that fractionate the δ 15 N in the soil are nitrification are denitrification and ammonia volatilization, in their study, there were greater δ 15 N in cultivated soils compared to native forests. The δ 15 N signature in plants can also increase when N fertilizer is applied (Santos et al, 2018). Santos et al (2018) reported an enrichment of the δ 15 N of Paspalum notatum roots after two years of N fertilization, the response was credited to a possible increase in the availability of SOM-N (rich in δ 15 N) after N fertilization, and due to the decrease in the C:N ratio.…”
Section: Soil C and N Isotopic Profilesmentioning
confidence: 99%
“…The δ 15 N signature in plants can also increase when N fertilizer is applied (Santos et al, 2018). Santos et al (2018) reported an enrichment of the δ 15 N of Paspalum notatum roots after two years of N fertilization, the response was credited to a possible increase in the availability of SOM-N (rich in δ 15 N) after N fertilization, and due to the decrease in the C:N ratio. Similar to our results, Franco et al (2015) evaluating areas of a chronosequence (forest-pasture-sugarcane) also reported higher δ 15 N in sugarcane areas.…”
Section: Soil C and N Isotopic Profilesmentioning
confidence: 99%